Investigation of electrochemical performance of an efficient Ti2O3–CeO2 nanocomposite for enhanced pollution-free energy conversion applications. (1st October 2021) - Swathi, S.; Yuvakkumar, R.; Kumar, P. Senthil; Ravi, G.; Velauthapillai, Dhayalan
Abstract: The development of an economical, abundant, stable, and greatly active electrocatalyst for water oxidation is extremely important for future energy conversion system. Electrochemical water splitting is a new move toward H2 and O2 gas production. It can be used in sustainable and pollution-free energy conversion applications. In this work, Ti2 O3 –CeO2 nanocomposites were successfully synthesized with different molar ratios by facile hydrothermal method for electrochemical water oxidation. Mixed phase structure of Ti2 O3 –CeO2 nanocomposites was confirmed by X-ray diffraction spectra and well identified by highest peak of Ti2 O3 in 2θ values of 33.0 and CeO2 in 2θ values of 28.5. The characteristic peaks from Raman and photoluminescence spectroscopy further confirmed Ti2 O3 –CeO2 nanocomposite formation. Existence of multidimensional nanostructures such as nanoparticles and small nanocubes of Ti2 O3 –CeO2 nanocomposites were investigated by scanning electron microscope images. Mesoporous nature of Ti2 O3 –CeO2 nanocomposites was further analyzed by Brunauer–Emmett–Teller analysis. The high surface area could benefit the Ti2 O3 –CeO2 nanocomposites with greatly improved oxygen evolution reaction (OER) performance. In three molar ratios, 1:3 M ratios of Ti2 O3 –CeO2 nanocomposites showed high catalytic action at overpotential of 244 mV. The best OER electrocatalyst was obtained by 1:3 M ratios of Ti2 O3 –CeO2 nanocomposites, which exhibited high current density and high specific capacitance values of 238 mA/g and 517 F/g, respectively. Therefore, Ti/Ce molar ratio played a crucial role in enhancing the OER performance. Highlights: 1:3 M ratio Ti2 O3 –CeO2 showed high catalytic action with 244 mV overpotential. OER electrocatalyst exhibited 238 mA/g current density and 517 F/g specific capacitance. In 16 h CA, 1:3 ratio Ti2 O3 –CeO2 exhibited 184 mA/g current density with 78% retention. Molar ratio of Ti/Ce participate crucial responsibility to enhance OER.